Roasting temperature and fat type influence cholesterol oxidation products, fatty acid composition, physicochemical properties and sensory attributes of beef sausages. - Kazeem Dauda Adeyemi; Latifat Opeyemi Abdulkadir (PLoS ONE)
The impact of fat type (FT) and roasting temperature (RT) on oxysterols, physicochemical properties and sensory attributes of beef sausages were investigated. Beef sausages were formulated with either 20% Beef tallow (BT), Palm olein (PO) or Soybean oil (SO), and oven-cooked at either 180oC for 30 min or 240oC for 15 min. The BT, PO, and SO sausages had the highest (P<0.05) levels of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA), respectively. Roasting at 240°C increased PUFA, MUFA, and total cholesterol levels, and reduced SFA moisture, and fat levels (P<0.05). The FT × RT interaction was significant for oxysterols, instrumental color and cook loss. The SO-180 sausages had higher levels of 7-ketocholesterol, 5,6β-epoxy cholesterol, cholesta-3,5-dien-7-one, and total oxysterols, but these levels decreased significantly at 240°C. The BT sausages exhibited lower overall cholesterol oxidation, though 22R-hydroxycholesterol was elevated at 180°C, while the PO sausages showed intermediate oxysterol oxidation, with 7α-hydroxycholesterol increasing at 240°C (P<0.05). The SO sausages had higher TBARS compared to other sausages (P<0.05). The BT sausages had greater lightness and lower cook loss at 240°C, while redness increased in both BT and SO sausages at 240oC (P<0.05). The BT sausages had higher hardness and chewiness. The PO sausages had better taste scores than the BT sausages, with similar results to SO sausages, and both PO and SO sausages had higher appearance and overall acceptance scores than the BT sausages. Fat type and roasting temperature synergistically affect oxysterol levels and quality attributes of beef sausages, highlighting the importance of selecting suitable fats and roasting conditions to ensure safety, nutritional value, and sensory quality.